DEVELOPMENT AND CHARACTERIZATION OF INDOMETHACIN-LOADED MUCOADHESIVE NANOSTRUCTURED LIPID CARRIERS FOR TOPICAL OCULAR DELIVERY - Niamprem, Pattravee; Srinivas, S. P.; Tiyaboonchai, Waree (International Journal of Applied Pharmaceutics, 2018)
Objective: To develop and characterize indomethacin loaded-nanostructured lipid carriers (IND-NLCs) for topical ophthalmic delivery with different particle sizes and polymer coating to improve the mucoadhesive property on the ocular surface. Methods: Nanostructured lipid carriers (NLCs) with different solid lipids and surfactants were prepared by the high-pressure homogenization technique. The optimized IND-NLCs was coated with polyethylene glycol 400 (PEG). The physicochemical properties and entrapment efficacy (EE) were examined. In vitro release studies were investigated using the shake-flask method. Ex vivo mucoadhesive studies were assessed by the wash-off test. In addition, the cytotoxicity was assessed by the short time exposure test. Results: IND-NLCs of ~300 and ~40 nm in diameter were successfully produced with a zeta potential of -30 mV and EE of 60–70 %. IND-NLCs prepared with Tween 80 as surfactant could be sterilized by autoclaving. The PEG coating of IND-NLCs did not affect either the particle size or EE. In vitro release showed a prolonged release for 360 min with a burst release of 50-60% occurring within 5 min. The smaller-sized IND-NLCs showed slightly faster release rates and better mucoadhesion to cornea compared to the larger IND-NLCs. PEG-coated IND-NLCs showed the highest mucoadhesion. In addition, IND-NLCs showed less cytotoxicity compared to IND alone. Conclusion: The small and PEG-coated NLCs represents a potentially useful carrier for safe delivery of indomethacin to the ocular surface with increased residence time.